Pembuatan Spectro-Animation Sebagai Media Pembelajaran Untuk Meningkatkan Pemahaman Siswa Pada Konsep Struktur Atom Bohr - Andri Agustina; Khoirul Anam; Sri Bulan (Balai Diklat Keagamaan Surabaya, 2022)
The purpose of this study to produce a learning media is spectro-animation used in learning Bohr atomic structure. Media spectro-animation consists of hardware integrated with animation software. This study used research and development (R&D) type Borg and Gall, through three phases: research design and literature studies, designing and manufacturing, and product development. Media spectro-animation is tested validation and feasibility tested by experts and chemistry teachers. The results of the validation got 94,5 and 94,0 average score with very good category. The final test product is done to 20 students of class X MIPA 1. There are increase understanding of the students' average score of 64 to pre-test mean score of post-test 81. The results of the t-test significance (sig) value 0.000 < 0.05, significant difference learning Bohr atomic structure before and after using the media. Feasibility by experts and chemistry teachers with indicators of effectiveness, efficiency and practicality media, each a score of 98,0 and 93,0 categories are very good. It can be concluded that media spectro-animation effective and can be implemented in learning Bohr atomic structure.